Different meanings a text may acquire: the case of Malachi 1:11 - S. D. Snyman (Acta Theologica)
This article illustrates how a text may acquire different meanings over years of investigation. On the basis of Malachi 1:11, the article demonstrates how this text was interpreted from various perspectives. Historical interpretation attempts to locate the meaning of the text either in the historical circumstances at the time of the origin of the text or at some undefined future time. A literary interpretation does not attempt to locate the text in history but rather tries to interpret it either as a hyperbole or metaphorically or by means of an intertextual investigation. At least eight different meanings were detected.